'How Do You Read It?' Rowan Williams, Marilynne Robinson and Mapping a Postmodern Reading of the Good Samaritan Parable. Issue 2 (9th September 2013) - Walker, Maxine E.
Abstract: To explicate the Good Samaritan parable, this paper employs Rowan Williams' interpretations of the parabolic imagination as explored in On Christian Theology (2000) and in Marilynne Robinson's novel Housekeeping (1980). Williams identifies reading strategies that open possibilities for reading parables through the lens of contemporary texts. Robinson's novel Housekeeping with its unconventional cast of unconnected women provides a contemporary way to explore the parable's opening question. Both Williams and Robinson, in their respective thoughts about 'housekeeping' as mutuality, discover that privileging established answers, conventional families and coded traditions interrogates the question 'who is my neighbor?' Both the theologian and the novelist explore behaviors that open the boundaries of family and traditions so that the elusive/allusive answer to the parable's question is found in unexpected haunting places with unfamiliar transients and on an ancient public road with one who has no name and voice.